Juridical Review Of Legal Protection For Domestic Workers (PRT) - Mario Borneo Tarigan (Journal of Law Science, 2021)
The existence of domestic workers or better known as domestic helpers is no stranger to the lives of Indonesian people, both in cities and in villages.The formulation of the problem in this study is: What is the Legal Position of Domestic Workers (PRT) in the Work Law in Indonesia? How are cases of domestic workers (PRT) resolved? What is the need for special arrangements for domestic workers (PRT) in the law.The method used is a normative research method which is a scientific research procedure to find the truth based on legal scientific logic from the normative side Legal Position of Domestic Workers (Prt) in Indonesian Work Law. Domestic workers are definitively recognized for their legal position as workers as referred to in Law Number 13 of 2003 concerning Manpower. According to Article 86 paragraph 1 of Law Number 13 of 2003 concerning manpower, it is stated that: “Every worker/labor has the right to obtain protection for (a) occupational safety and health, (b) morals and decency; and (c) treatment in accordance with human dignity and religious values. The consensus deliberation process is carried out between domestic workers and their employers and/or domestic service providers as the simplest step to resolve disputes. Deliberations were taken for the first time without the involvement of local government officials. However, if necessary, local government officials can serve as witnesses in the deliberations. In making decisions through deliberation to reach consensus, time is limited so that it does not drag on and a sense of justice is fulfilled in an effort to provide legal certainty for the parties The need for special arrangements for home workersDomestic workers (PRT) are an important source of livelihood for women and men in Southeast Asia. Because the work is done within the household and is considered informal work, there are no regulations governing it, and as a result it often goes unnoticed. This is a category of work that is in dire need of legal and social protection, as its workers are vulnerable to harassment and exploitation during recruitment and placement, during work, and upon return to their place of origin. This paper summarizes the main problems faced by domestic workers, as well as the obstacles experienced in obtaining their rights.